2018
DOI: 10.1002/dta.2391
|View full text |Cite
|
Sign up to set email alerts
|

Mixed intoxication by the synthetic opioid U‐47700 and the benzodiazepine flubromazepam with lethal outcome: Pharmacokinetic data

Abstract: Novel synthetic opioids and benzodiazepines are an emerging trend on the narcotic drugs market. We present a lethal case of U-47700 and flubromazepam poisoning. A 24-year-old man suffered apnoea after the consumption of the synthetic opioid U-47700 in combination with the benzodiazepine flubromazepam. After reanimation and hospital admission, hypoxic cerebral damage and severe brain oedema were stated. Six days after admission, mechanical ventilation was discontinued, and the patient died. Seven blood serum sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 23 publications
2
28
2
Order By: Relevance
“…Examples of sedative designer drugs and reference substances for comparison. Full names of the substances are provided in the supplementary information either designer opioids alone or designer opioids combined with other psychoactive substances (Coopman et al 2016a, b;Cunningham et al 2016;Dussy et al 2016;Dwyer et al 2018;Elliott et al 2016;Fels et al 2017Fels et al , 2019Fort et al 2016;Garneau et al 2019;Gillespie et al 1982;Guerrieri et al 2017;Helander et al 2017a;Karinen et al 2014;Koch et al 2018;Kriikku et al 2019;Kronstrand et al 2014;Krotulski et al 2018;Martucci et al 2018;McIntyre et al 2015bMcIntyre et al , 2016McIntyre et al , 2017Mohr et al 2016;Nash et al 2019;Ojanperä et al 2006;Papsun et al 2016;Partridge et al 2018;Poklis et al 2016;Richeval et al 2019;Ruan et al 2016;Sofalvi et al 2017;Staeheli et al 2016;Swanson et al 2017;Takase et al 2016;Vorce et al 2014;Yonemitsu et al 2016). Frisoni and colleagues recently published an overview of opioid-related fatalities that were attributed to synthetic opioids (Frisoni et al 2018).…”
Section: Adverse Effects Of Synthetic Opioidsmentioning
confidence: 99%
“…Examples of sedative designer drugs and reference substances for comparison. Full names of the substances are provided in the supplementary information either designer opioids alone or designer opioids combined with other psychoactive substances (Coopman et al 2016a, b;Cunningham et al 2016;Dussy et al 2016;Dwyer et al 2018;Elliott et al 2016;Fels et al 2017Fels et al , 2019Fort et al 2016;Garneau et al 2019;Gillespie et al 1982;Guerrieri et al 2017;Helander et al 2017a;Karinen et al 2014;Koch et al 2018;Kriikku et al 2019;Kronstrand et al 2014;Krotulski et al 2018;Martucci et al 2018;McIntyre et al 2015bMcIntyre et al , 2016McIntyre et al , 2017Mohr et al 2016;Nash et al 2019;Ojanperä et al 2006;Papsun et al 2016;Partridge et al 2018;Poklis et al 2016;Richeval et al 2019;Ruan et al 2016;Sofalvi et al 2017;Staeheli et al 2016;Swanson et al 2017;Takase et al 2016;Vorce et al 2014;Yonemitsu et al 2016). Frisoni and colleagues recently published an overview of opioid-related fatalities that were attributed to synthetic opioids (Frisoni et al 2018).…”
Section: Adverse Effects Of Synthetic Opioidsmentioning
confidence: 99%
“…A large number of studies have reported the identification of U-47700 in toxicological samples and information on pharmacokinetics is starting to be published. Koch et al [ 123 ] reported the analysis of samples from a patient who was admitted to hospital following the alleged smoking of an opioid. Serum and urine samples were taken and flubromazepam, its metabolite hydroxyl-flubromazepam and U-47700 were detected.…”
Section: Toxicology Metabolism and Toxicovigilancementioning
confidence: 99%
“…A fatal intoxication related to the effect of the U-47700 in combination with the benzodiazepine flubromazepam was recently reported (Koch et al, 2018 ). A 24 year-old man suffered apnoea and after reanimation and hospital admission, hypoxic cerebral damage and severe brain oedema were stated.…”
Section: Resultsmentioning
confidence: 99%
“…Presently, several intoxication cases related to the consumption of U-47700 alone, or in combination with other drugs, were recently reported (Coopman et al, 2016 ; Elliott et al, 2016 ; Mohr et al, 2016 ; Armenian et al, 2017 ; Dziadosz et al, 2017 ; Jones et al, 2017 ; McIntyre et al, 2017 ; Papsun et al, 2017 ; Vo et al, 2017 ; Koch et al, 2018 ), but reference toxic and lethal concentrations in body fluids and organs are not yet available for U-47700. Intoxication cases involving U-47700 are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%